Meaning in life and adolescent self-control: Effect of perceived social support and its gender differences - Liu, Yafei; Di, Siyu; Shi, Yaohui; Ma, Chao (Frontiers in Psychology, 2022)
The objective of this study is to investigate the relationship between meaning in life and adolescent self-control, as well as the role of perceived social support and gender in this pathway. For this purpose, a total of 936 adolescents from two high schools were selected as subjects in this study. The Meaning in Life Scale, the Self-Control Scale, and the Perceived Social Support Scale were used for the research. The results obtained in this study have shown that meaning in life is a significant positive predictor of adolescent self-control and perceived social support. In addition, perceived social support partially mediates the relationship between meaning in life and self-control. Further, it has been found that gender moderates the second half of the pathway of the mediation model of meaning in life on self-control, specifically, perceived social support is a stronger predictor of self-control for girls than for boys. The results of this study suggest that enhancing perceived social support promotes self-control in adolescents with lower meaning in life, and this process is more pronounced in females.